Increased LEF1 Expression and Decreased Notch2 Expression Are Strong Predictors of Poor Outcomes in Colorectal Cancer Patients. Issue 5 (26th September 2013) - Wang, Wen-Juan; Yao, Yu; Jiang, Li-Li; Hu, Ting-Hua; Ma, Jie-Qun; Ruan, Zhi-Ping; Tian, Tao; Guo, Hui; Wang, Shu-Hong; Nan, Ke-Jun
Abstract : Background/Objective . We aimed to examine the expression of lymphoid enhancer factor 1 (LEF1) and Notch2 in colorectal cancer (CRC) and their association with clinicopathologic variables and CRC patients' prognosis. Methods . Immunohistochemistry, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blot analysis were performed to assess the expression of LEF1 and Notch2 in 184 patients with CRC. Results . We observed a strong negative correlation between LEF1 expression and Notch2 expression (P < 0.001 ). Both LEF1 mRNA and protein expression increased while the Notch2 mRNA and protein expression decreased in tumor specimens compared with the matched paratumorous normal tissue (P < 0.001 ). An increase in LEF1 protein expression was significantly associated with lymph node metastases, distant metastasis, advanced TNM (tumor-node-metastasis) stage, and shorter overall survival. A decrease in Notch2 protein expression was associated with poorly differentiated tumors, lymph node metastases, distant metastasis, advanced TNM stage, and shorter overall survival of patients. In the multivariate Cox regression analysis, the LEF1 protein expression (P < 0.001 ), Notch2 protein expression (P < 0.001 ), TNM stage (P < 0.001 ), and the combination of increased LEF1 protein coexpression and decreased Notch2 protein coexpression (P < 0.001 ) were found to be independent prognostic indicators in CRC. Conclusion . Our results suggest that increased LEF1 coexpression and decreased Notch2 coexpression represent a risk factor for poor overall survival of CRC patients.